2022
DOI: 10.1186/s12864-022-08675-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of OSCA gene family in Solanum habrochaites and its function analysis under stress

Abstract: Background OSCA (hyperosmolality-gated calcium-permeable channel) is a calcium permeable cation channel protein that plays an important role in regulating plant signal transduction. It is involved in sensing changes in extracellular osmotic potential and an increase in Ca2+ concentration. S. habrochaites is a good genetic material for crop improvement against cold, late blight, planthopper and other diseases. Till date, there is no report on OSCA in S. habrochaites. Thus, in this study, we perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Generally, the subcellular localization helps to decipher its cellular function. Previous studies have reported that OSCA proteins were localized in the cell membrane in other plants [ 18 , 45 ]. In the current study, both the in silico prediction and the subcellular localization results indicated that the HvOSCA family members are localized in the inner-membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the subcellular localization helps to decipher its cellular function. Previous studies have reported that OSCA proteins were localized in the cell membrane in other plants [ 18 , 45 ]. In the current study, both the in silico prediction and the subcellular localization results indicated that the HvOSCA family members are localized in the inner-membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Plants have evolved complex signal transductions and stress resistance mechanisms to survive the harsh weather conditions of the external environmental [2,4]. The OSCA genes induce the increase in the Ca 2+ concentration in the cytoplasm during hyperosmotic stress, which is an essential response mechanism of plants to drought and salt-induced osmotic stress [7,12,15]. The OSCA gene family members in plants that carry the DUF221 domain have been identified in plants such as: A. thaliana [7], O. sativa [11], Z. mays [30], V. radiata [12], and P. trichocarpa [13].…”
Section: Discussionmentioning
confidence: 99%
“…To understand the functional characteristics and evolutionary relationship of the OSCA gene family in L. chinense, a phylogenetic tree was constructed using the full-length sequences of the OSCA proteins in L. chinense (11), A. thaliana (15), O. sativa (11), and P. trichocarpa (17). Based on the phylogenetic tree, the OSCA proteins can be divided into four subgroups (Clade 1-4) (Figure 3).…”
Section: Phylogenetic Analysis and Classification Of L Chinense Osca ...mentioning
confidence: 99%
See 1 more Smart Citation
“…OSCA family genes have been studied in a variety of plants and found to play potential roles in plant stress resistance ( Li et al, 2015 ; Yin et al, 2021 ; Tong et al, 2021 ; Miao et al, 2022 ). Following the publication of the genomes of the sunflower and other Compositae plants, the evolution of this gene family in Compositae has not been systematically studied.…”
Section: Introductionmentioning
confidence: 99%